Bureacratic disappearance in Mexico: Ethnography and debate over a “local political category” - de la Serna-Alegre, Andrea (2025)
In this article, the category “bureaucratic disappearance” is analyzed. This category is used in Mexico to refer to a mode of disappearance perpetrated by state institutions and their agents. This category politicizes the idea of “forensic crisis,” which obscures the causes of the problem insofar as it characterizes it as something extraordinary. The objective of the article is to demonstrate how the idea of “bureaucratic disappearance” is being converted into a “local political category,” coined by the families of disappeared people to enunciate and denounce phenomena that are supposedly uncommon. The analysis is sustained by data obtained through two years of ethnography conducted in the framework of a collaborative agreement with the collective Uniendo Esperanzas. With the women that make up this group, it was possible to conduct a “bureaucracy ethnography in accompaniment,” which enabled observing the processes that are described and analyzed in the article. Finally, several lines of reflection are formulated in relation to the form in which routine practices of bureaucrats constitute serious corporate violence, among which bureaucratic disappearance stands out. The main conclusion is that bureaucratic routines in searching for people and in disappearances are understood in terms of forensic information fragmentation and express forms of stateness.